(Poly)phenols of apples contribute to in vitro antidiabetic properties: Assessment of Canada's Apple Biodiversity Collection. Issue 2 (7th September 2022) - Yu, Cindy H. J.; Migicovsky, Zoë; Song, Jun; Rupasinghe, H. P. Vasantha
Societal Impact Statement: Apples are affordable and accessible fruit with tremendous biodiversity. Among over 10, 000 identified apple cultivars, only a few are commercially available. Habitual fruit consumption is correlated with the prevention of Type 2 diabetes and related complications. Particularly, (poly)phenols found in apples are major contributors to their antidiabetic properties. Here, we have screened (poly)phenol‐rich extracts of 476 apple accessions in Canada's Apple Biodiversity Collection for antidiabetic properties. The results of this work provide insights into the prevention and management of Type 2 diabetes by identifying high (poly)phenol‐containing specialty apples for use in fresh fruit form or value‐added functional food ingredients. Summary: The recent trend in sedentary lifestyles and nutritionally‐imbalanced diets has elevated the prevalence of Type 2 diabetes in many parts of the world. Some pharmacological glycemic management can cause undesirable gastrointestinal side effects or hypoglycemia. Thus, there is a growing interest in safe glycemic management using dietary (poly)phenols. In this study, (poly)phenol‐rich extracts of 476 apple accessions from Canada's Apple Biodiversity Collection (ABC) and six major apple (poly)phenols were assessed for in vitro antidiabetic properties against the activities of α‐glucosidase, α‐amylase, and dipeptidyl peptidase‐4 (DPP‐4) and the formation of advanced glycation end products (AGE). Apple (poly)phenol extracts varied in their antidiabetic activities in a dose‐dependent manner. High (poly)phenol‐containing apples demonstrated that their total phenolic contents (TPC) were inversely correlated with the IC50 values of α‐glucosidase, α‐amylase, and AGE formation, but not DPP‐4. Concentrations of major (poly)phenol compounds such as procyanidin B2, phloridzin, and epicatechin in apples were significantly inversely correlated with IC50 values of α‐glucosidase in the high (poly)phenol‐containing apples. High TPC apples are not suitable for marketing for fresh fruit consumption due to bitterness and astringency; however, these apples show potential to use in the development of value‐added functional food ingredients or nutraceuticals for blood glucose management. The high TPC apple, "S23‐03‐749, " an advanced breeding line of dessert apple, presents a novel option as a specialty apple cultivar for the dietary management of glycemia. Abstract : Apples are affordable and accessible fruit with tremendous biodiversity. Among over 10, 000 identified apple cultivars, only a few are commercially available. Habitual fruit consumption is correlated with the prevention of Type 2 diabetes and related complications. Particularly, (poly)phenols found in apples are major contributors to their antidiabetic properties. Here, we have screened (poly)phenol‐rich extracts of 476 apple accessions in Canada's Apple Biodiversity Collection for antidiabetic properties. The results of this work provide insights into the prevention and management of Type 2 diabetes by identifying high (poly)phenol‐containing specialty apples for use in fresh fruit form or value‐added functional food ingredients. Summary: Les pommes sont des fruits abordables et accessibles avec une formidable biodiversité. Parmi plus de 10, 000 cultivars de pommiers identifiés, seuls quelques‐uns sont disponibles dans le commerce. La consommation habituelle de fruits est corrélée à la prévention du diabète de type 2 et des complications associées. En particulier, les (poly)phénols présents dans les pommes sont des contributeurs majeurs à leurs propriétés antidiabétiques. Ici, nous avons examiné des extraits riches en (poly)phénols de 476 pommes de la Collection Biodiversité des pommes du Canada pour leurs propriétés antidiabétiques. Les résultats de ces travaux donnent un aperçu de la prévention et de la gestion du diabète de type 2 en identifiant des pommes de spécialité à haute teneur en (poly)phénols à utiliser sous forme de fruits frais ou d'ingrédients alimentaires fonctionnels à valeur ajoutée.